The Impact of Mosque Typo-Morphology on Users’ Visual Comfort - Lana Abubakr Ali; Mzoori, Faris Ali Mustafa (Zanco Journal of Pure and Applied Sciences, 2025)
Visual comfort is a fundamental human goal impacted by the perception of interior architectural geometry via vision as one of five human sensors. The geometrical and spatial qualities of an architectural space, including area, size, dimension, volume, and human scale, among others, affect the perceived space. Furthermore, it is necessary to note that daylight influences the perceived indoor space. The mosque was the most important building in Islamic civilization because it serves as the principal place of worship. The prayer hall (or haram) is an essential part of the mosque. Mosque typo morphology is the focus of this research, which examines the building from a spatial and volumetric perspective. This study investigates how prayer hall's most popular typo-morphological characteristics may affect users' visual comfort. This study examines mosque typo-morphological design using mixed-method qualitative and quantitative evaluations. A qualitative method was used to describe the mosques through architectural drawings. A quantitative questionnaire survey was conducted to receive experts' feedback on mosque visual comfort satisfaction using VR. The study's findings indicate that creating spatial openness and visible volume in prayer hall configurations clear of obstacles and effective integration with monumental scale and vertical visual proportion significantly impacts visual comfort. The study concluded that the levels of visual comfort in mosque prayer halls differ according to the typo-morphological design characteristics of mosques. The current study contributed to linking the known mosque prototypes and the level of visual comfort for users through an in-depth comparative-analytical study.